PROBLEM OF TRUST TO POWER IN RUSSIA - Alexander V. Tsarev; Victor V. Krupenkov; Tatiana K. Minenko (Статистика и экономика, 2016)
Currently the topic of trust is very important. The most important problem of our country at the present stage performs low level of trust relationships between people, business, government. Generally trust is an integral part of society and is manifested in all its spheres. Directly, this paper analyzes the trust in the political sphere. Mostly, the task is to assess the level of public confidence in the existing government in our country.